Anion receptor functionalized mesoporous material - Wong, Wen Yee, 1988-; Salasiah Endud; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011